Polyphenol-enriched extract of oil palm fronds (Elaeis guineensis) promotes vascular relaxation via endothelium-dependent mechanisms. - Abeywardena, Mahinda; Runnie, Irine; Nizar, Mohd; Suhaila, Momamed; Head, Richard (John Wiley & Sons, 2002)
Plant-based polyphenolic compounds have been reported to possess cardiovascular health benefits. Several dietary sources, including herbs and spices, fruits and vegetables, and tea and wine, contain an array of biologically active compounds that have been shown to be effective in retarding oxidation of low-density lipoproteins (LDL) and promoting vascular relaxation. In the present study four different plant sources, both edible and non-edible, were evaluated for potential activity. Organic extracts enriched in polyphenols were prepared from palm fronds (Elaesis guineensis); lemongrass (Cymbopogon citrates); papaya shoots (Carica papaya) and green chilli (Capsicum frutescenes) and tested for their ability to prevent in vitro oxidation of LDL, and for potential vascular relaxation actions. Rings of rat thoracic aorta and isolated perfused mesenteric vascular beds were mounted in organ baths, contracted using a half-maximal dose of noradrenaline and exposed to cumulative additions of test extracts. Palm frond extract resulted in considerable relaxation (>75%) in both preparations and was found to be endothelium-dependent as removal of endothelium or inhibition of endogenous nitric oxide (NO) led to a total loss in relaxant activity. Lemongrass extract caused a greater relaxation action in the mesenteric preparation compared to aortic rings, and appears to be mediated via NO-independent and non-prostanoid mechanisms. Of the extracts tested, palm fronds also demonstrated the highest antioxidant capacity, as determined by the ferric reducing activity/potential assay, and resulted in a significant delay (P < 0.05) in the oxidation of LDL. Collectively, these preliminary findings lend further support to the potential cardiovascular actions of plant polyphenols and also identify oil palm fronds as containing constituents that promote vascular relaxation via endothelium-dependent mechanisms.